Representation of Feminism in the Kethoprak 1756 (Pitoelas Seket Enem) Performances - Hery Riyanto; Mutiara Arista (Javanologi: International Journal of Javanese Studies, 2024)
Kethoprak is a traditional Javanese theater art. In its performances, kethoprak often displays various kinds of stories which also contain various kinds of messages and social criticism. One of the  kethoprak performances that represent feminism is the performance entitled 1756 (Pitoelas Seket Enem) presented by KKTT Wiswakarman. The 1756 performance is a performance that adopts a story about the upheaval of the Javanese war carried out by Mangkunegara I with the help of female warriors from Ladrang Mangungkung with the main character named Gantari.This research is an interpretive qualitative research using a feminist and semiotic approach as a tool to explore the research. Feminism theory is used to dissect the representation of feminism in the entire performance, while semiotic theory is used to dissect the symbols related to the performance. This research data is a representation of feminism in the kethoprak dish entitled 1756 by KKTT Wiswakarman while the data sources for this research include books, and previous research which can be used as a valid reference source to support research. The result of this research is that the kethoprak performance performed by KKTT Wiswakarman with the title 1756 contains a representation of feminism which is seen in the character named Gantari. This representation of feminism can be seen in the gestures, expressions, dialogue, and lighting of the character Gantari during the performance.